LOCAL WISDOM LEARNING STRATEGIES IN EARLY CHILDHOOD EDUCATION (CASE STUDY: EARLY CHILDHOOD EDUCATION IN THE SPECIAL REGION OF YOGYAKARTA AND SOUTH SUMATRA) - Muhakkamah M. Ahdad; Suyadi Suyadi; Novita Loka; Eko Purnomo; Mansur Mansur (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
Local wisdom in children's education is challenging to find today. Even though the introduction of local wisdom from an early age is outstanding in developing various aspects of child development. The purpose of this study was to determine the learning strategy of local wisdom in two provinces. This research is a type of field research with a case study approach. Sample selection conducted based on purposive sampling in one ECCE institution in South Sumatra and the Special Region of Yogyakarta. The PAUD institutions that were sampled in this study were TK Al-Ittifaqiyah Indralaya South Sumatra and PAUD Griya Yogyakarta. The data collection techniques used were observation, interviews and documentation. While data analysis using Miles and Huberman techniques is through the process of data collection, data reduction and conclusions. The results of the study found that teachers use goods in the surrounding environment in learning local wisdom. The dance strategy is the strategy used by TK Ittafiqayah while the traditional Javanese art strategy is the strategy used by in learning local wisdom.